MOTIF MONUMEN SEBAGAI IDE READY TO WEAR DENGAN SABLON POLYFLEX - Edi Suwasana; Dwy Nurcahyati (Garina, 2021)
The Lembu Sora Building Monument and the Pure Milk Monument are monuments located in Boyolali Regency, Central Java which will be used as ready to wear motifs with the aim of introducing the area as the largest producer of cow's milk in Central Java. Taking pictures of the motifs uses deformation techniques and distortion techniques which are realized by polyflex screen printing techniques on ready to wear. Based on the problems and objectives, this study aimed to determine the application of the image of the Lembu Sora Building Monument and Pure Mil Monument as a motif on ready to wear with Polyflex Screen Printing Technique. The research methods used were observation, documentation, and literature review. This final project was completed by: creating designs, preparing tools and materials, conducting trials on selecting fabrics and polyflex types, determining sizes, creating ready-to-wear patterns, cutting fabrics, pressing the coating material, carrying out the polyflex screen printing process, ready-to-wear sewing process, and completion. Furthermore, the polyflex screen printing process on ready-to-wear included the following steps: creating polyflex screen printing designs, printing designs with a cutting machine, peeling polyflex (polyflex cleaning), gluing polyfex on the fabric, and finishing, which was the process of removing the masking from the polyflex sheet. Researchers suggest that during the pressing process on polyflex, it is required to alter the temperature and time with the type of polyflex. According to the recommendation that can be utilized, the pressing process on polyflex for temperature and duration must be adjusted to the type of polyflex.